NEW APPROACHES IN ASSESSING THE COORDINATION ABILITIES OF STUDENT YOUTH - Tretyakov, A.A.; Strelkova, Ya.A.; Krivchenkov, V.V.; Oleinik, A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the effectiveness of the test for assessing the coordination abilities of students of higher educational institutions. Methods and structure of the study. The experiment involved 5-year students of universities in the city of Belgorod in the amount of 300 people. They were offered to perform motor and computer test tasks. Results and conclusions. During the training of pilots, the "Gorelov Test" was used for a comprehensive assessment of coordination abilities. It was proposed to use this test to assess the coordination abilities of students. As a result of testing, data were obtained, the average time of the test in girls is better (7.92±0.25 s) than in boys (8.31±0.33 s). The average time spent on fulfilling 1 stimulus out of 9 was also calculated. And in this indicator, the time for girls (0.88±0.02 s) is better than for boys (0.92±0.03 s). When performing the test, the girls made fewer mistakes. It can be said that the Gorelov Test makes it possible to assess the coordination abilities associated with the body's ability to coordinate motor actions. As a result of the study, a comprehensive method for assessing the coordination abilities of students was determined. Validity assessment of the Gorelov Test showed a high correlation with a number of motor and computer tests.